Kassandra: A Framework for Distributed Simulation of Heterogeneous Cooperating Objects. - Figura, Richard; Shih, Chia-Yen; Ceriotti, Matteo; Fu, Songwei; Brockmann, Falk; Nebot, Héctor; Alarcón, Francisco; Kropp, Andrea; Kondak, Konstantin; Schwarzbach, Marc; Jiménez Viguria, Antidio; Mulero-Pázmány, Margarita Cristina; et al. (Elsevier, 2016)
To address the heterogeneity and scalability issues of simulating Cooperating Objects (COs) systems, we propose Kassandra, a conceptual framework for enabling distributed COs simulation by integrating existing simulation tools. Moreover, Kassandra exploits the communication middleware used by real-world COs as underlying communication mechanism for integrating Kassandra-enabled simulation tools. In this way, real-world COs can be included with simulated objects in a seamless way to perform more accurate system performance evaluation. Moreover, such a hardware-in-the-loop approach is not limited to pre-deployment performance analysis, and can offer possibilities to analyse performance at different phases of CO applications. The concept of Kassandra has been carried out in the EU PLANET project. In this paper, we introduce the Kassandra framework components and show their interactions at different phases for node deployments in PLANET use cases. The result demonstrates the applicability of Kassandra to facilitate the development of CO applications.
https://openpolicyfinder.jisc.ac.uk/id/publication/11438
Keywords: Detectores; Heterogeneous cooperating objects; Sensors; Drones